2018
DOI: 10.1016/j.ultrasmedbio.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Piezo1 but Not NaV1.2 Channels by Ultrasound at 43 MHz

Abstract: Ultrasound (US) can modulate the electrical activity of the excitable tissues, but the mechanisms underlying this effect are not understood at the molecular level or in terms of the physical modality through which US exerts its effects. Here, we report an experimental system that allows for stable patch-clamp recording in the presence of US at 43 MHz, a frequency known to stimulate neural activity. We describe the effects of US on two ion channels proposed to be involved in the response of excitable cells to U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 68 publications
6
119
1
1
Order By: Relevance
“…Stimulation of stretch activated channels was proposed as the underlying mechanism. Interestingly, Piezo1 can be activated by ultrasound [35]. Though the significance of Piezo1 in physiological insulin secretion is not evident from our study, using mechanosensitive Piezo1 induction as a strategy to induce insulin secretion has clear clinical potential and warrants further investigation [34].…”
Section: Discussionmentioning
confidence: 78%
“…Stimulation of stretch activated channels was proposed as the underlying mechanism. Interestingly, Piezo1 can be activated by ultrasound [35]. Though the significance of Piezo1 in physiological insulin secretion is not evident from our study, using mechanosensitive Piezo1 induction as a strategy to induce insulin secretion has clear clinical potential and warrants further investigation [34].…”
Section: Discussionmentioning
confidence: 78%
“…This possibility is likely given the emerging view that the e↵ects of ultrasound on neurons are of a mechanical kind. In particular, the mechanical forces associated with propagating ultrasound displace membranes and this way open mechanosensitive ion channels (Tyler, 2011;Kubanek et al, 2018;Prieto et al, 2018). It has been demonstrated that such mechanosensing molecules adapt to repetitive mechanical stimulation (Ge↵eney and Goodman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this theoretical model, and the work in small animal models, the effect of tFUS parameters on neuronal excitation in humans is not well understood empirically and indeed the basic putative mechanisms of how mechanical energy affects neuronal excitability is still largely theoretical [28][29][30][31]. There is evidence for US to affect certain mechanosensitive channels [32,33] but the proliferation and density of these channels in human CNS is not well understood and the contribution of these channels to pyramidal excitation and neurovascular coupling is also unclear.…”
Section: Discussionmentioning
confidence: 99%